Cernea’s classification of the External Branch of the Superior Laryngeal Nerve during Microscopic Thyroidectomy at Gandaki Medical College, Pokhara - Dubey, Tulika; Sigdel, Brihaspati; Nepali, Rajendra; KC, Neeraj (Journal of Gandaki Medical College-Nepal, 2021)
Background: Preservation of the external branch of the superior laryngeal nerve (EBSLN) during thyroidectomy is important because its injury may lead to frequent occurrence of vocal fatigue and the inability to perform phonation. The objective of the study was to identify and classify the nerve as per Cernea’s classification using operating microscope during thyroidectomy Method: Between January 2017 to December 2019, we evaluated 50 patients for the position of external branch of superior laryngeal nerve, who underwent microscopic thyroid surgeries in the department of ENT- head and neck surgery at Gandaki Medical College. Results: In our study, we dissected a total 59 superior poles of thyroid from 50 patients and identified the nerve in all the cases. Of the total superior poles, 36 (61.01%) had type IIa EBSLN among which 24 was on the right side and 12 on the left followed by 19 (32.20%) patients with type IIb EBSLN among which 8 on right and 11 on left side. There were only 4 poles (6.77%) of type I with 3 on the right and 1 on the left side. Conclusion: The EBSLN can be very efficaciously identified during a microscope assisted thyroidectomy. Cernea type 2a and 2b EBSLNs are in position to be at high risk of injury during ligation of the superior vascular pedicle, which can be avoided by prompt identification through a microscope and a meticulous extra capsular dissection technique.